Reading plus comprehension: nightnigale press: early stage 1 - Lewis, Ruth; Burgess, Therese (Nightingale Press Warners Bay, 1998)
Reading Plus Comprehension focuses on improving reading skills through engaging texts and comprehension exercises. It typically includes various types of passages, such as fiction, nonfiction, and poetry, accompanied by questions that assess understanding.